Date Palms In The Quran: The Descriptions - Zainan Nazri, Mohd Khairul Nizam; Mohamed Yusoff, Adnan; Nazri, Nur Farhah Zainan; Khalaf, Najm Abdul Rahman; Abdul Rahman, Asma (Universiti Sains Malaysia, 2016)
Dates have been recorded as part of human diet since antiquity and throughout major human civilizations including the biblical traditions. Dates are a robust, flexible and long lasting plant that can survive in a harsh environment. In Arabic, it is known as al-nakhl, which etymologically means “good, nourishing and nice smelling”. Dates are mentioned in the Qur’an for 27 times as nakhl, nakhla, alnakhlah, nakhil, and others; ascertaining its significance. Therefore, this study attempts to analyze the interpretations of the verses according to significant books of commentary. By applying textual analysis method, the study found that Allah has revealed that the date palm has soft spadix producing clusters of dates hanging low and near; being arranged and layered one above another. It also has tough trunk; most suitable for crucifixion and to be attached to during childbirth. Allah uses the hollow and uprooted trunks as parables and proclaims that some of the date palms come from a single stem root. Allah conveys that the date palm produces sheathed fruit-stalks; enclosing dates as well as fruits of different taste. He also admits that strong drink i.e. liquor could be derived from dates i.e. before its prohibition and describes the date palm stone in three different places. Simultaneously, He sets forth parables with three small parts hidden in the nucleus of dates known as al-fatil, al-naqir and al-qitmir. Allah has also described the date palm using different terms known as shajarah tayyibah, kull hin and min linah.